TINGKAT KONDISI FISIK ATLET UKM BOLATANGAN PUTRI DI UNIVERSITAS NEGERI SURABAYA - ABIDAH, KHIKMATUL; PERWIRA BAKTI, ANANDA (Jurnal Kesehatan Olahraga, 2018)
AbstractThe physical condition of athletes UKM handball daughter at the State University of Surabaya in every match susceptible to fatigue. The purpose of this study was to determine the level of physical condition UKM handball Women Athletes at the State University of Surabaya.The targets of this research is 14 female UKM handball athletes at the State University of Surabaya. Research conducted at the International Futsal GOR Surabaya State University. The research instrument used in this study is the Test Run 30M to measure speed, test Sit and Reach to measure flexibility, Illinois Agility Run Test to measure agility, Test Push-Up for measuring the strength of the arm muscles, tests Medicine Ball to measure the explosive power of the arm muscles and Multistage Fitnes Test to measure cardiac and respiratory endurance.The results of the series of tests showed that the average Tests Run 30M for 5:40 seconds into the category of being, on average Tests Sit and Reach of 37.96 cm fall into either category, the average Illinois Agility Test Run of 19.66 seconds in the medium category, average Test Push-Up of 34.43 times in the category of less, on average Test Medicine Ball of 3.62 m / s in the category of medium and average of 32.76 Multistage Fitnes Test O2 / kg / min in the category less.The conclusion from this study that the level of physical condition of athletes handball Women at the State University of Surabaya in the category of being with a percentage of 50% of the overall results of the physical condition of athletes UKM handball components daughter at the State University of Surabaya.Keywords : Physical Condition, handball